Effect of Ashwagandharishta on the lipid profile of male and female rats (Jahangirnagar University Journal of Biological Sciences, 2021)
The effect of Ashwagandharishta on the lipid profile and chronic toxicity of both male and female Albino rats were observed for 51 days. Our results demonstrate that the treatment of the plant extract failed to exhibit any statistically significant change (increase/ decrease) in the serum cholesterol (Total), high density lipoprotein (HDL), low density lipoprotein (LDL) and triglyceride of the male rats. But the female rats showed highly (p